Bibliometric analysis of research on soil arsenic during 2005–2016 - Cui, Meng-qian; Wu, Chuan; Jiang, Xing-xing; Liu, Zi-yu; Xue, Sheng-guo (Journal of Central South University, 2019)
Bibliometrics is an important branch in the field of information science, and it is widely used in many disciplines in modern research. A current active research subject can be analyzed and summarized from many aspects, such as the core institutions, core authors, highly cited papers, and keywords by using bibliometrics. This paper describes a bibliometric analysis regarding soil arsenic content by using the database from Web of Science to compare relevant research from work done domestically and abroad from 2005 to 2016. The results show that the relevant publications in China and overseas both dramatically increased from 2009, which indicates that research activity is expanding. The USA produced 27.3% of all relevant articles followed by China with 26.9% and India with 9.5%. Key issues mainly focused on agriculture and environmental science. Major journals studied include the following: Science of the Total Environment, Environmental and Experimental Botany, Environmental Pollution, Chemosphere, Journal of Hazardous Materials, Journal of Environmental Chemical Engineering, Journal of Geochemical Exploration, Ecotoxicology and Environmental Safety, Environmental Research, Talanta, and Applied Geochemistry. These are the most important journals in this field. In light of cooperation between countries, it is clear that China and the United States occupy the leading position.